Kegiatan Pengabdian kepada Masyarakat: Edukasi Pemasaran Digital sebagai Upaya Penguatan Jiwa Entrepreneur - Deavvy M.R.Y Johassan; Ronnie Sirait; Siti Meisyaroh (Institut Bisnis dan Informatika Kwik Kian Gie, 2026)
The development of information technology and the internet has changed the way businesses market their products. However, many aspiring entrepreneurs and MSMEs do not yet have adequate knowledge about digital marketing. This lack of understanding has the potential to hinder competitiveness, narrow market reach, and reduce the chances of business sustainability. The objectives of this PkM activity are: (1) Providing a basic understanding of digital marketing, including the concepts of branding, market segmentation, and online promotion strategies, (2) Improving participants' ability to utilize digital platforms, such as social media, marketplaces, and content design applications, (3) Cultivating an entrepreneurial spirit through motivation, case studies, and practical marketing plan preparation, and (4) Encouraging participants to implement digital marketing strategies to increase business added value. This activity integrates two scientific fields, namely informatics and management, to provide comprehensive understanding to participants. In the informatics aspect, participants are introduced to informatics concepts such as Marketing Information Systems, Search Engine Optimization (SEO), Digital Content Creation, Data Analytics, and Social Media Marketing. In the management aspect, participants are invited to understand the importance of the impact on increasing the marketing capacity of MSMEs, but also provide important contributions to the development of management science, especially related to digital marketing models, MSME development strategies, and the implementation of management theory in the context of a technology-based local economy. Digital marketing education not only teaches promotional techniques, but also instills creative, adaptive, and innovative ways of thinking..